Pension crisis or pension rethink? - Hoskins, D (Foundation for Law, Justice and Society, 2008)
There exists a widespread conviction that pension protection, along with many other social benefits, is slowly being eroded as responsibility for insurance and the associated costs are shifted steadily from government and employers to individual citizens and their family members. But was there really a ‘golden age’ of pension protection? If so, what are the causes that undermined these guarantees, and what are the policy parameters and defining characteristics that have shaped pension policies during the last couple of decades?